Les relations commerciales entre l’Inde et l’Asie centrale entre 1550 et 1920 : des échanges intenses et diversifiés - Claude Markovits (Cahiers d’histoire)
This article deals with a little-known aspect of the economic history of Central Asia, the intense exchanges it maintained for nearly four centuries with India. From the sixteenth century, as numerous documents attest, Indian merchants roamed the region, making silk from India for textiles and other products, and bringing back to India precious metals and metals, while d Other merchants were present in the export of Turkish horses for the cavalry of the Indian states. Indian commercial presence continued until the Revolution of 1917, although the Russian conquest of the 1870s started a decline in the caravan trade. The emphasis is on the role played by the merchants of Shikarpur, a locality in Sindh (in present-day Pakistan), thanks to the exhumation of a forgotten archive.